Repatriation of the Brain Drain to Brain Gain Dichotomy from Urban Areas to Rural Areas: Decentralizing Development - SELELO, Mohale Ernest; MOKOELE, Ngoako Johannes; MNISI, Pearl Thobeka (International Journal of Environmental, Sustainability, and Social Science, 2023)
The development stagnation or lack thereof of rural areas in South Africa is fast becoming unprecedented because of the loss of much human capital to urban areas. Therefore, the paper aims to conceptualize and analyze the implications of the brain drain in rural areas. The central argument of this paper is that the unprecedented relocation of youthful and educated human capital from rural to urban areas perpetuates underdevelopment in these areas. This shift of skilled and educated population can be noted as brain drain and with the antagonist arguing that it is brain gain in urban areas. Consequently, rural areas experienced depopulation, which did not spark interest in investment toward development. In that, the proliferation of underdevelopment facets in rural areas can be attributed to the loss of losing human capital from people with skills, knowledge, expertise, abilities, and capabilities migrating from rural to urban areas. Therefore, most rural areas need more capacitated people to enhance their socioeconomic conditions. This conceptual paper adopts a literature-based methodology to assess and critique the repatriation of the brain drain from urban areas to rural areas and decentralize development to benefit people in rural areas. It finds that rural areas still need to be developed due to brain drain (loss of human capital) and rural-urban migration. It recommends that people with the necessary skills, knowledge, and experience return to the communities to decentralize and reindustrialize rural areas for better living standards.